Real-Time Monitoring and Historical Analysis of Rainfall and its Impacts on Urban Areas - Cruz, Fábio Victorino da; Miranda, Fabio; Paes, Aline; Oliveira, Daniel de; Lage, Marcos (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2025)
Climate change, combined with unplanned urban growth, has intensified the occurrence of natural disasters in developing countries like Brazil, leading to severe floods and significant loss of life. Recent events, such as the 2024 floods affecting 90% of the cities in Rio Grande do Sul, highlight the urgency of improving disaster response. Governments and citizens increasingly share large volumes of disaster-related data, offering opportunities for better mitigation strategies. This paper presents PluvWeb, a visual system that integrates heterogeneous data sources to support the analysis of rainfall impacts in urban areas. The system automates landslide response routes, detects floods from traffic cameras, and analyzes rainfall patterns, with effectiveness shown in case studies from a Brazilian city.